Effect of Power and Feed to Solvent Ratio Toward Yield of Essential Oil from Crystal Guava Leaves (Psidium guajava) Using Microwave Hydroditillation - Caecilia Pujiastuti; Nove Kartika Erliyanti; Anugerah Dany Priyanto (Future Science)
The essential oil from crystal seedless guava leaves has several utilization as an antioxidant and antimicrobial active compound. Essential oil extraction with maceration and conventional method has many disadvantages, so the microwave hydrodistillation method is used as an alternative to optimizing its quantity and quality. This research aims to obtain the effect of microwave power and feed to the solvent ratio toward essential oil yield. The extraction of essential oil used crystal guava leaves with feed and solvent ratio (w/v) 1:4; 1:5; 1:6; 1:7. The extraction process was carried out at atmospheric pressure and 100 oC with an electrical power of microwave from 300, 450, and 600 watts over 3 hours. The result shows that microwave power and the ratio of feed to solvent (F/S) give a significant ratio to essential oil yield. Its yield rises significantly along with increasing microwave power and ratio of feed and solvent. The highest yield is obtained at 600 watts and 1:7 (w/v) ratio that is 1.0 %.